2015
DOI: 10.1126/scitranslmed.3009986
|View full text |Cite
|
Sign up to set email alerts
|

The nicotinic α6 subunit gene determines variability in chronic pain sensitivity via cross-inhibition of P2X2/3 receptors

Abstract: Chronic pain is a highly prevalent and poorly managed human health problem. We used microarray-based expression genomics in 25 inbred mouse strains to identify dorsal root ganglion (DRG)-expressed genetic contributors to mechanical allodynia, a prominent symptom of chronic pain. We identified expression levels of Chrna6, which encodes the α6 subunit of the nicotinic acetylcholine receptor (nAChR), as highly associated with allodynia. We confirmed the importance of α6* (i.e., α6-containing) nAChRs by analyzing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
69
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 81 publications
7
69
0
Order By: Relevance
“…That nAChRs subunits have a role on nocifensive behavior and on the antinociceptive effects of nicotine has also been previously shown (Bagdas et al, 2015; Damaj et al, 1999; Freitas et al, 2015; Saika et al, 2015; Wieskopf et al, 2015; Xanthos et al, 2015; Yalcin et al, 2011). In studies using nAChR agonists and antagonists as well as mice with nAChR subunits null mutations, researchers have shown that nAChRs containing α3, α4, α5, α6, α7, β2, and β4 subunits are involved in modulating nocifensive behaviors in response to acute noxious thermal stimuli (Damaj et al, 2007; Damaj et al, 1999; Marubio et al, 1999) and in response to inflammatory and neuropathic processes (AlSharari et al, 2012; Bagdas et al, 2015; Damaj et al, 1999; Freitas et al, 2015; Saika et al, 2015; Wieskopf et al, 2015; Xanthos et al, 2015; Yalcin et al, 2011).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…That nAChRs subunits have a role on nocifensive behavior and on the antinociceptive effects of nicotine has also been previously shown (Bagdas et al, 2015; Damaj et al, 1999; Freitas et al, 2015; Saika et al, 2015; Wieskopf et al, 2015; Xanthos et al, 2015; Yalcin et al, 2011). In studies using nAChR agonists and antagonists as well as mice with nAChR subunits null mutations, researchers have shown that nAChRs containing α3, α4, α5, α6, α7, β2, and β4 subunits are involved in modulating nocifensive behaviors in response to acute noxious thermal stimuli (Damaj et al, 2007; Damaj et al, 1999; Marubio et al, 1999) and in response to inflammatory and neuropathic processes (AlSharari et al, 2012; Bagdas et al, 2015; Damaj et al, 1999; Freitas et al, 2015; Saika et al, 2015; Wieskopf et al, 2015; Xanthos et al, 2015; Yalcin et al, 2011).…”
Section: Discussionmentioning
confidence: 57%
“…In studies using nAChR agonists and antagonists as well as mice with nAChR subunits null mutations, researchers have shown that nAChRs containing α3, α4, α5, α6, α7, β2, and β4 subunits are involved in modulating nocifensive behaviors in response to acute noxious thermal stimuli (Damaj et al, 2007; Damaj et al, 1999; Marubio et al, 1999) and in response to inflammatory and neuropathic processes (AlSharari et al, 2012; Bagdas et al, 2015; Damaj et al, 1999; Freitas et al, 2015; Saika et al, 2015; Wieskopf et al, 2015; Xanthos et al, 2015; Yalcin et al, 2011). Others have also shown that mice with null mutations of α4, α5, or β2 have decreased response to the analgesic effects of nicotine, but intact response to the antinociceptive effects of morphine (Damaj et al, 2007; Marubio et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…We calculated that 51%–77% of human eGenes are also expressed in mouse DRGs. From microarray data, we found 3rd quartile gene expression above 1st quartile overall expression for 333 (77%) out of 432 matched eGenes (Figure S5a, GEO set GSE65997) (Wieskopf et al, 2015). From single-cell mouse RNA-Seq data, we found expression of 3rd quartile above zero for 376 (51%) out of 731 matched eGenes (Usoskin et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…AK092568 is not the gene suggested by the original publication, which speculated on the role of chaperonin-containing-TCP1-complex-5 gene ( CCT5 , P=1.83e-01) and/or family with sequence similarity 173, member B ( FAM173B , P=4.36e-01). Interestingly, AK092568 is situated within death-associated protein ( DAP ) gene, which is a positive mediator of programmed cell death induced by interferon-gamma, and can potentially regulate expression of DAP , which can be found in mouse DRG (GEO set GSE65997 (Wieskopf et al, 2015)), in both neuronal and non-neuronal DRG cell types (2.5 and 1.0 rpkM respectively (Usoskin et al, 2015), Figure S5c). As such, the potential role of AK092568 in pain is at least as likely as CCT5 or FAM173B .…”
Section: Resultsmentioning
confidence: 99%
“…α6 subunits are also expressed by a subset of retinal ganglion cells, a sparse population of neurons in the dorsal lateral geniculate nucleus of the thalamus, and are widely expressed in several layers of superior colliculus (Mackey et al, 2012). α6 subunits are also expressed in medial habenula to interpeduncular nucleus pathway (Henderson et al, 2014, Shih et al, 2014), and have recently been shown to play an important role in nociception via their expression in spinal cord (Wieskopf et al, 2015). Although the DA system is the most logical candidate to mediate nicotine-elicited locomotor activation, several of these areas also have a plausible link to the locomotor system.…”
Section: Discussionmentioning
confidence: 99%